Are Your Data Good Enough:: A Checklist for Mining Prospects - Dewing, Keith (Geoscience Canada, 2007)
This checklist is intended to help geologists collect or review geological data on mining prospects in a manner that will conform to the increasingly stringent reporting requirements. Survey, assay, and geological data are the key initial inputs required to build a robust computer-based resource model. Once the resource model is built, a geologist reviewing the model should understand the methods and assumptions used in interpolating from the initial data to the gridded resource model. Closer cooperation between project geologists and resource modellers should improve the way data are collected initially as well as identifying biases, weakness and inconsistencies within the resource model.